Generalization of digital innovation for financial inclusion by means of market creation through regulation and governance - Varsolo Sunio; Jaime Mendejar; Justin Reginald Nery; Jose Paolo Carlos (Global Transitions, 2023)
Achieving financial inclusion in shorter timeframes is a grand societal challenge that can be addressed by digital technology. Nonetheless, how an innovative digital technology gets generalized is understudied in the literature. We present the generalization of a cloud-based core banking system to drive financial inclusion in the Philippines. We draw our material from the case of cloud-based core banking system adoption in the Philippines. Our results show that market formation is essential to the generalization, and this can be accomplished through a mix of laissez-faire and dirigisme mechanisms. Pure laissez-faire mechanisms alone, with minimal intervention from the central bank, may drive the generalization of digital innovations. Nonetheless, for the generalization of cloud digital technology to happen at an accelerated pace, the central bank must intervene more proactively, especially in establishing an industry-wide digital financial ecosystem. Furthermore, for the generalization of cloud digital technology to truly contribute to the societal mission of financial inclusion, the central bank ought to take the lead as a meta-governor directing the various elements of the digital finance ecosystem. Our study provides a nuanced understanding of the interplay between laissez-faire and dirigisme in the genesis of markets for digital innovations in pursuit of financial inclusion.